Clinical and Oculomotor Correlates With Freezing of Gait in a Chinese Cohort of Parkinson’s Disease Patients - Wu, Li; Wang, Qin; Zhao, Lei; Jiang, Chun-Yan; Xu, Qian; Wu, Si-Cheng; Dong, You-Rong; He, Qing; Chen, Wei; Liu, Jian-Ren (Frontiers in Aging Neuroscience, 2020)
Accumulating evidence suggests that freezing of gait (FOG) is a unique gait disturbance in Parkinson’s disease (PD), and its pathophysiology is not fully elucidated. The present study aims to investigate the clinical and oculomotor associations with FOG in Chinese PD patients. From Jan 2017 to Dec 2019, a total of 210 PD patients were consecutively registered for FOG evaluation based on item-3 of the Freezing of Gait Questionnaire (FOGQ). We explored the demographic, motor, and non-motor symptom differences in FOG positive (PD+FOG, n = 45) vs. negative (PD-FOG, n = 165) group. In addition, 40 PD patients and 37 healthy controls (HC) also underwent oculomotor test via videonystagmography (VNG). Visually guided saccade (VGS) latency, saccade accuracy and gain in smooth pursuit eye movement (SPEM) at three frequencies of horizontal axis were compared among PD+FOG (n = 20), PD-FOG (n = 20), and HC (n = 37). Compared with PD-FOG, PD+FOG had longer disease duration, more severe motor symptoms, lower cognitive scores, more severe depressive and autonomic impairments, as well as higher daily levodopa equivalent dosage. FOG occurred more frequently in patients with wearing-off. VNG subgroup analysis demonstrated that PD+FOG had prolonged saccade latency and decreased saccade accuracy relative to PD-FOG or HC. SPEM gain at 0.1 and 0.2 Hz was also decreased in PD+FOG compared with HC. Furthermore, prolonged saccade latency was correlated with higher FOGQ scores in PD patients. Our results verify that PD with FOG patients suffer from more severe motor and non-motor symptoms, indicating more extensive neurodegeneration. Prolonged saccade latency could be a practical oculomotor parameter both for identification and progression of FOG in PD.